Sistem Pendukung Keputusan Untuk Seleksi Jabatan Dengan Menggunakan Metode Topsis (Studi Kasus: Kantor Camat Lais) - Darmansah Darmansah; Sandhy Fernandez; Ike Kurnia Putri; M. Yoka Fathoni; Sena Wijayanto (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Along with the development of computers and technology, the business world is becoming increasingly competitive. One of the most important things that must be anticipated by the company/organization is a reliable and qualified workforce in each position. Currently, the selection process for determining answers in the Lais sub-district is still going on manually and has not used information technology, thus making it difficult for the sub-district government to position staff according to the area of ​​expertise possessed by each sub-district employee. From these problems it is necessary to make a decision support system to facilitate the sub-district in conducting the selection process for determining employee positions. In making this decision support system the author uses the TOPSIS method. The results of this study resulted in a computerized decision support system based on a website and for the application of the Topsis method, it was found that alternative 1 was identified as the best alternative compared to other alternatives with a value of 0.661180544.